2017
DOI: 10.1175/bams-d-15-00324.1
|View full text |Cite
|
Sign up to set email alerts
|

Climate Engine: Cloud Computing and Visualization of Climate and Remote Sensing Data for Advanced Natural Resource Monitoring and Process Understanding

Abstract: The paucity of long-term observations, particularly in regions with heterogeneous climate and land cover, can hinder incorporating climate data at appropriate spatial scales for decision-making and scientific research. Numerous gridded climate, weather, and remote sensing products have been developed to address the needs of both land managers and scientists, in turn enhancing scientific knowledge and strengthening early-warning systems. However, these data remain largely inaccessible for a broader segment of u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
142
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 259 publications
(166 citation statements)
references
References 33 publications
3
142
0
5
Order By: Relevance
“…Increasing R s values (combined with weakening winds from Figure and Table ) can explain the observed slight temperature change in irrigated areas in a period when CR‐estimated ET rates were also increasing during 1981–2007. A general R s increase in the Central Valley over the modeling period is further supported by the Climate Engine (http://app.climateengine.org/) data visualization site (Huntington et al, ). The dropping R n values during 1981–2007 are then the result of increasing thermal radiation from the land surface due to insolation‐driven elevated surface temperatures further boosted by failing winds.…”
Section: Resultsmentioning
confidence: 99%
“…Increasing R s values (combined with weakening winds from Figure and Table ) can explain the observed slight temperature change in irrigated areas in a period when CR‐estimated ET rates were also increasing during 1981–2007. A general R s increase in the Central Valley over the modeling period is further supported by the Climate Engine (http://app.climateengine.org/) data visualization site (Huntington et al, ). The dropping R n values during 1981–2007 are then the result of increasing thermal radiation from the land surface due to insolation‐driven elevated surface temperatures further boosted by failing winds.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we demonstrate a transferrable approach for understanding and monitoring responses of meadow ecosystems to climate variability using remote‐sensing‐based indicators and a water balance model. Platforms such as Google Earth Engine (Gorelick et al, ) and cloud‐computing applications such as Climate Engine (http://climateengine.org/; Huntington et al, ) have provided free access to—and highly efficient processing of—climate and remotely sensed information that can be used to quantify ecological sensitivities to climate and monitor other drivers of change ranging from site specific (e.g., Hausner et al, ) to regional (as demonstrated in this study) scales.…”
Section: Discussionmentioning
confidence: 96%
“…Landsat satellite imagery has proven to be an effective and efficient data source for monitoring key ecological attributes of meadows and riparian systems over extensive areas and time periods (Ager & Owens, ; Cartwright & Johnson, ; Cohen & Goward, ), including above‐ground biomass, which relates to vegetation structure, function and composition, and vegetation water content. Recent advances in cloud computing (Gorelick et al, ) now permit efficient application of algorithms across the Landsat satellite image archive for long‐term monitoring of groundwater dependent ecosystems with respect to climate and management (Dauwalter, Fesenmyer, Miller, & Porter, ; Hausner et al, ; Huntington et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, changes in snowpack affect the timing and volume of run‐off. Rising winter air temperatures reduce snowpack by decreasing the fraction of precipitation that falls as snow (Huntington et al, ). It can also cause snowmelt to occur earlier in the season.…”
Section: Methodsmentioning
confidence: 99%